Membangkitkan Tradisi Budaya dan Hukum Adat Melayu Untuk Mewujudkan Kesalehan Sosial di Kalangan Millenial - Yudhi Novriansyah; Khairun A Roni; Supriyati Supriyati; Darham Darham; Herawati Herawati (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
In order to increase understanding of the millennial generation and as a forum for preserving Jambi Malay cultural values, the Working Group for the Study of Socio-Economic and Cultural Issues at the Research and Community Service Institute (LPPM) of Muara Bungo University in collaboration with the Association of Indonesian Muslim Intellectuals (ICMI) Bungo Regional Organization held a Seminar and Discussion with the theme Reviving Malay Cultural Traditions and Customary Laws to Realize Social Piety Among Millennials. This activity involved elements of the Student Executive Board (BEM) organization and all Faculty of Economics students participating in UMB and Regional Insight courses. It is hoped that from the implementation of this seminar the millenial’s generation will have an understanding of being heirs to the nation's cultural wealth. Participants will be able to understand the customary laws and dress code of Malay people and the processions and attire of Malay brides.